2014
DOI: 10.3382/ps.2013-03650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postmortem aging on marination performance of broiler breast pectoralis major categorized by color lightness

Abstract: The objective was to evaluate the effect of postmortem aging on marination performance of early-deboned chicken breast fillets (pectoralis major) with different color lightness. Effects of marination on muscle shear force were also determined. Early-deboned (2 h postmortem) broiler butterfly fillets were visually selected based on their color lightness (pale, normal, and dark) from a commercial plant. The individual butterfly fillets were separated into left and right fillets. One of them was used for 6-h mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The information regarding the nutritional value, physicochemical attributes and postmortem changes in the duck meat is of prime importance for meat processing industries to consider the use of duck meat for manufacturing different meat-based products (Huda et al, 2011). Zhuang et al (2014) assessed the effects of postmortem aging on the marination performance of broiler breast and observed that aging prior to marination did not affect marinade absorption. Sodium chloride and phosphate-based marination is categorized as an alkaline marinade resulting in a significant increase in duck breast pH (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The information regarding the nutritional value, physicochemical attributes and postmortem changes in the duck meat is of prime importance for meat processing industries to consider the use of duck meat for manufacturing different meat-based products (Huda et al, 2011). Zhuang et al (2014) assessed the effects of postmortem aging on the marination performance of broiler breast and observed that aging prior to marination did not affect marinade absorption. Sodium chloride and phosphate-based marination is categorized as an alkaline marinade resulting in a significant increase in duck breast pH (Table 2).…”
Section: Discussionmentioning
confidence: 99%